ANALISA PENGARUH KEPUASAN KERJA TERHADAP KINERJA KARYAWAN (STUDI KASUS PADA PT. BANK MANDIRI (Persero) Tbk MAKASSAR) - Adrianus Parenden (Jurnal Bisnis dan Kewirausahaan, 2015)
This study aimedn to clarify whether the variable Job Satisfaction significant influence on employee performance at PT. Bank Mandiri (Persero) Tbk. Makassar as well as to determine which variables are the dominant influence of the two variable Job Satisfaction on the performance of employees at PT. Bank Mandiri (Persero) Tbk Makassar. The sample of using purposive sampling method is directly choosing 50 persons of the employees. The data collection methods that used were interview the parties that involved with the issues being discussed directly and gave questionnaires to the employees in accordance with the research conducted. The data were analyzed with using Qualitative and Quantitative Methods that using five formulas; Simple Regression Analysis, Correlation Analysis, Test T-test, F test and the coefficient of determination (R2) test with the aid of SPSS 18.0 software for windows. The results showed that jointly Job satisfaction significantly influence the performance of employees at PT. Bank Mandiri (Persero) Tbk Makassar. Variable Job Satisfaction regression coefficients positive (+) indicates a unidirectional relationship, in other words, Job Satisfaction will improve the performance of employees at PT. Bank Mandiri (Persero) Tbk Makassar. The correlation or the relationship between Job Satisfaction Employee Performance Performance Work with PT. Bank Mandiri (Persero) Makassar is very strong for (r = 0.923) and the coefficient of determination or the number of Rsquare is 0.853